The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1758-5996-3-23
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between measures of insulin resistance in fasting and non-fasting blood

Abstract: BackgroundEpidemiological investigation of insulin resistance is difficult. Standard measures of insulin resistance require invasive investigations, which are impractical for large-scale studies. Surrogate measures using fasting blood samples have been developed, but even these are difficult to obtain in population-based studies. Measures of insulin resistance have not been validated in non-fasting blood samples. Our objective was to assess the correlations between fasting and non-fasting measures of insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…In agreement with the results from previous studies on leptin concentration and body weight, we found that serum leptin concentrations were dependent on gender and BMI (Hassink et al 1996;Blum et al 1997;Garcia-Mayor et al 1997). Our findings of a more advanced pubertal development together with higher leptin levels are also in agreement with a study showing leptin concentrations to be higher in post-pubertal girls than in prepubertal girls (Demerath et al 1999).…”
Section: Discussionsupporting
confidence: 95%
“…In agreement with the results from previous studies on leptin concentration and body weight, we found that serum leptin concentrations were dependent on gender and BMI (Hassink et al 1996;Blum et al 1997;Garcia-Mayor et al 1997). Our findings of a more advanced pubertal development together with higher leptin levels are also in agreement with a study showing leptin concentrations to be higher in post-pubertal girls than in prepubertal girls (Demerath et al 1999).…”
Section: Discussionsupporting
confidence: 95%
“…Such conditions can drive profound endocrine disruptions in other species, including disturbed insulin-glucose metabolism. Therefore, we assessed non-fasting insulin and glucose as measures of insulin sensitivity, as used in population-based studies of humans (Hancox and Landhuis, 2011) and for routine diagnosis of insulin resistance and metabolic syndrome in the horse (Divers, 2008;Treiber et al, 2005). The non-fasting insulin reference interval for free-ranging black rhinos of 1.8-19.4 lU/mL was similar to the 2-15 lU/mL reported for the horse (Nadeau et al, 2006;Pagan et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Briefly, we applied this non-parametric, robust estimation method following box-cox transformation and outlier removal. Additionally, indices of insulin secretion (insulin-to-glucose ratio, I/G) and insulin sensitivity (glucose-to-insulin ratio, G/I; quantitative insulin sensitivity check index, QUICKI; reciprocal of the square root of insulin, RISQI) validated for the human (Hancox and Landhuis, 2011;He et al, 1999;Katz et al, 2000;Kronborg et al, 2007;Sullivan et al, 2004), cat (Bjornvad et al, 2014) and horse (Frank, 2009;Kronfeld et al, 2005;Treiber et al, 2005) were calculated to allow cross-species comparisons. The insulin sensitivity index QUICKI was calculated as 1/[log(insulin)+log(glucose)], and RISQI was determined as insulin À0.5 .…”
Section: Discussionmentioning
confidence: 99%
“…While serum concentrations of insulin are markedly affected by composition and time from recent meals, serum concentrations of leptin seem less affected. However, estimates of insulin resistance measured in non-fasting blood seem to correlate well with values obtained in fasting blood samples (Hancox and Landhuis, 2011), thus suggesting that non-fasting blood samples can be used. On the other hand we cannot exclude possible bias related to taking the blood samples in the fasting state has remained.…”
Section: Discussionmentioning
confidence: 97%